Cocirculation of two dengue virus serotypes in individual and pooled samples of Aedes aegypti and Aedes albopictus larvae - José Eduardo Marques Pessanha (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: To detect dengue virus, eggs of Aedes sp were collected in the city of Belo Horizonte, Brazil, in 2007. METHODS: Egg samples were subsequently hatched and the larvae were tested for the presence of dengue virus RNA by RT-PCR. RESULTS: Among the Aedes aegypti larvae samples, 163 (37.4%) out of 435 were positive, including 32 (10.9%) of 293 individual larvae samples concomitantly positive for two serotypes. CONCLUSIONS: Virological surveillance detecting coinfected vectors in the field could represent an important strategy for understanding the numerous factors involved in the transmission and clinical presentation of dengue.